From regional imbalances to latecomer advantage: Phosphorus pollution and economic development in the Yangtze economic belt - Li, Jincheng; Zhang, Xinyue; Kahil, Taher; Chen, Dongni; Wang, Guangyao; Xu, Shasha; Zhang, Yang; Chen, Yan (Ecological indicators, 2025)
•Identifies two inflection points in the NAPI-GDP relationship within the YREB.•Reveals regional disparities in phosphorus input dynamics and EKC turning points.•Demonstrates the effectiveness of targeted environmental policies in reducing NAPI.•Provides a replicable framework for balancing economic growth and environmental sustainability. Phosphorus pollution from human activities threatens ecosystems, especially in rapidly developing regions. This study aims to assess the spatiotemporal dynamics of net anthropogenic phosphorus input (NAPI) in the Yangtze River Economic Belt (YREB) from 1980 to 2020, focusing on the balance between economic growth and environmental sustainability. Employing the Logarithmic Mean Divisia Index (LMDI) and Environmental Kuznets Curve (EKC) frameworks, the study identifies two key inflection points in the NAPI-GDP per capita relationship, marking shifts in phosphorus input trends. Results indicate that NAPI in the YREB increased significantly from 1980 to 2020, mainly due to fertilizer application (62.36%) and economic growth (77.8%). Regional disparities persist: the eastern region reached its EKC turning point earlier, while the western region benefited a “latecomer advantage,” achieving reductions at a lower economic threshold. By 2020, most YREB regions had crossed their EKC turning points, signaling a transition to coordinated economic and environmental progress. Policies such as the “Ten Water Regulations” significantly reduced phosphorus inputs, particularly in high-pollution areas. Continued investment in sustainable agricultural practices, green technology, and targeted regional strategies is essential to bridge phosphorus management gaps. The findings provide critical insights into phosphorus pollution dynamics in a major economic corridor and demonstrates a replicable framework for integrating environmental considerations into economic planning. These results contribute to developing actionable strategies for cleaner production and long-term sustainability in rapidly developing regions.